Nasal Polyp-Derived Mesenchymal Stromal Cells Exhibit Lack of Immune-Associated Molecules and High Levels of Stem/Progenitor Cells Markers - Oliveira, Pedro Wey Barbosa de; Pezato, Rogério; Agudelo, Juan Sebastian Henao; Perez-Novo, Claudina Angela; Berghe, Wim Vanden; Câmara, Niels Olsen; de Almeida, Danilo Candido; Gregorio, Luís Carlos (Frontiers in Immunology, 2017)
Mesenchymal stromal cells (MSCs) are considered adult progenitor stem cells and have been studied in a multitude of tissues. In this context, the microenvironment of nasal polyp tissue has several inflammatory cells, but their stroma compartment remains little elucidated. Hence, we isolated MSCs from nasal polyps (Polyp-MSCs) and compared their molecular features and gene expression pattern with bone marrow-derived MSCs (BM-MSCs). Initially, both Polyp-MSCs and BM-MSCs were isolated, cultivated and submitted to morphologic, differentiation, phenotypic, immunosuppressive and gene expression assays. Compared to BM-MSCs, Polyp-MSCs showed normal morphology and similar osteogenic/adipogenic differentiation potential, but their immunophenotyping showed lack of immune-associated molecules (e.g. CD117, HLA-DR, PDL-1 and PDL-2) which was linked with less immunoregulatory abilities such as: i) inhibition of lymphocytes proliferation and ii) Treg expansion. Furthermore, we detected in the Polyp-MSCs a distinct gene expression profile in comparison with BM-MSCs. Polyp-MSC expressed higher levels of progenitor stem cells specific markers (e.g. CD133 and ABCB1), while BM-MSCs showed elevated expression of cytokines and growth factors (e.g. FGF10, KDR and GDF6). The gene ontology analysis showed that the differentially modulated genes in Polyp-MSC were related with matrix remodeling process and hexose and glucose transport. For BM-MSCs, the highly-expressed genes were associated with behavior, angiogenesis, blood vessel morphogenesis, cell-cell signaling and regulation of response to external stimulus. Thus, these results suggest that Polyp-MSCs, while sharing similar aspects with BM-MSCs, express a different profile of molecules, which presumably can be implicated in the development of nasal polyp tissue.